Zakat and poverty alleviation in a secular state: the case of Muslim minorities the Philippines - Gamon, Alizaman Dumangcag (2017)
There are twelve millions of Filipinos living in an extreme poverty. Despite of having a well-crafted government model for poverty alleviation, the state roles in managing charities to alleviate people’s sufferance from economic deprivation are very minimal. By reason of the state’s strict adherence to secularism, the operation of Islamic institutions at the social level is deemed unconstitutional. It is unfortunate that the dynamics of Islamic social financial institutions i.e. zakat, waqf and sadaqah are not reflected in the economic road map for the reconstruction of Autonomous Region in Muslim Mindanao, particularly the rehabilitation of Marawi City after the war. This study examines the collaborative efforts of government agencies and Muslim organizations towards the gradual revival of Islamic social financial institutions for their role and capabilities in poverty alleviation within context of a secular state. It will also identify whether or not the current practices in managing zakat and poverty alleviation can meet the necessary needs of the poor. Researchers analytically study the policies as well as problems faced by these organizations in managing the zakat institutions in the Philippines. The methodology used is based on qualitative method through documents analysis. This study found out that due to mismanagement, zakat fails to eliminate or reduce the poverty of the Muslim minorities in the Philippines.